Highly sensitive phage-magnetic-chemiluminescent enzyme immunoassay for determination of zearalenone. (30th September 2020) - Liu, Ruxia; Shi, Ruirui; Zou, Wenting; Chen, Wenhua; Yin, Xianchao; Zhao, Fengchun; Yang, Zhengyou
Highlights: A novel phage-magnetic-chemiluminescent enzyme immunoassay for zearalenone analysis. The combined application of phage-mimotope and immunomagnetic beads in immunoassay. The whole incubation time of the immunoassay is 40 min. The limit of detection of the immunoassay for corn samples is 0.3 μg/kg. The immunoassay strategy can be effective for the analysis of mycotoxins. Abstract: Here we demonstrate a novel phage-magnetic-chemiluminescent enzyme immunoassay (P-MCLEIA) for detection of zearalenone (ZEN). The P-MCLEIA was more efficient than conventional ELISA through several improvements. In the P-MCLEIA, magnetic nanoparticles were replaced of microplates as solid phases to reduce the whole incubation time within 40 min. Phage-mimotope was replaced of chemosynthetic antigen to improve the sensitivity of immunoassay. Chemiluminescence substrate was replaced of chromogenic substrate to further improve the sensitivity. The IC50 value of P-MCLEIA was 31.4 pg/mL, which was about 11 times lower than that of phage-magnetic-enzyme linked immunosorbent assay (P-MELISA) and 72 times lower than that of conventional ELISA. The LOD of P-MCLEIA was 4.3 pg/mL. Recovery study of P-MCLEIA was performed by analyzing ZEN levels in spiked corn samples, intra- and inter-assay recoveries were 80.0–119.8% and 82.7–112.7%, respectively. Furthermore, parallel analysis of natural corn samples showed a good correlation between the P-MCLEIA and high performance liquid chromatography.